True Detectives: Mediological Reflections on Public Evidence of the Jihadist- Motivated Terror Attack of 2 November 2020 in Vienna, via Edgar Allan Poe, Matthew Buckingham, and Xaver Bayer; with an Amendment on Lament (Response to 7 October) - Zolles, Christian (Wiener Digitale Revue, 2024)
peer-reviewed Focusing on the terror attack on 2 November 2020 in Vienna, the article reflects on the media dispositifs that generate public evidence in connection with terrorist crimes. To this end, investigative visual arts—works and ‘window pane scenarios’ by Edgar Allan Poe, the New York artist Matthew Buckingham and the Austrian writer Xaver Bayer—will first be used to reflect on the general prerequisites for the detective and photographic gaze, which developed from early experiences of the big city crowd. Subsequently, the Vienna attack is analysed as a media event by looking in detail at the journalistic reporting and interaction in the social media as well as the court proceedings that were conducted two years later against the six men who were accused of involvement in the attack. The concluding section aims to show the extent to which a media-critical philological investigation can add an important complementary perspective to the public processes of reviewing and negotiating events of terror. It can succeed in addressing spaces of silence that must be reserved without restriction for the victims of violence beyond a collective horizon of witnessing and opinionforming—to be expected a common sense that was fatally suspended in many respects on and after 7 October 2023. Der Beitrag reflektiert am Beispiel des Anschlags vom 2. November 2020 in Wien die medialen Dispositive, die im Zusammenhang mit terroristischen Verbrechen öffentliche Evidenz erzeugen. Hierfür werden zunächst über investigative visual arts – Werke und ‚Fensterscheiben-Szenarien‘ von Edgar Allan Poe, des New Yorker bildenden Künstlers Matthew Buckingham sowie des österreichischen Schriftstellers Xaver Bayer – die generellen Voraussetzungen für den detektivischen und fotografischen Blick reflektiert, wie er sich aus den frühen Großstadterfahrungen heraus entwickelt hat. Im Anschluss daran wird der Anschlag in Wien als mediales Ereignis vorgestellt, indem detailliert auf die journalistische Berichterstattung und die Interaktionen in den sozialen Medien sowie auf die Gerichtsverfahren eingegangen wird, die zwei Jahre später über sechs Mitverdächtige geführt wurden. Im abschließenden Teil wird gezeigt, inwiefern eine medienkritische philologische Untersuchung den öffentlichen Aufarbeitungs- und Aushandlungsprozessen von Terrorereignissen eine bedeutende ergänzende Perspektive hinzufügen kann. Sie kann es schaffen, Räume der Stille zu adressieren, welche den Opfern der Gewalt abseits eines kollektiven Horizonts der Zeugenschaft und Meinungsbildung uneingeschränkt vorbehalten bleiben müssen – an sich ein common sense, der am und nach dem 7. Oktober 2023 in vielen Bereichen fatalerweise aussetzte.